Effects of Differently Treated Cassava Flours Blended with Bambara Groundnut Flour on the Bread Making Potential of Two Nigerian Wheat Cultivars - Agbara, G. I.; Babagana, B. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
Studies involving the use of composite flour for baked goods are unending for reasons such as high quest for functional foods, unsustainable wheat import and nutritional enhancement of baked goods. In this study, cassava flour (CF) was differently treated: roasted (Cr), fermented (Cf), oven dried (Co) and sundried (Cs) before separately blended with flours from de-braned, hammer milled Nigerian wheat varieties, Norman (Wn) and Atilla (Wa) in the ratio of 75:25. The blends (8) were used to bake breads. Refined commercial wheat flour bread was the control. The breads and the flour blends were evaluated for physical, chemical and sensory qualities using standard procedures. Results revealed that the blends had higher ash (0.57-1.31%) and carbohydrate (76.69-81.03%), lower moisture (8.27-10.30%), protein (6.91-10.10%) and crude fat (1.28-2.45%) and desirable higher water and oil absorption capacities (0.85-1.30mg/g) and (1.16-1.40g/g) respectively. There were improvements in the swelling power (6.91-10.10g/g) and solubility (4.00-7.00%) due to CF addition. The ash, protein, and fibre of the treated breads were higher, while the carbohydrate and fat were lower than in the wheat bread. Specific loaf volume (SLV) of wheat bread (2.58ml/g) and bread with oven dried CF (2.61ml/g) were higher; others had lower SLV not significantly different from each other (p>0.05). There were significant increase(p<0.5) in the mineral contents of the composite bread, more in the bread with sun and oven dried CF. The least amounts were recorded in the breads containing fermented CF for obvious reasons. As for wheat flour and the flour blends, they varied respectively: K 84.04-140.56, Ca 20.29-38.79, Mg 17 51-32.32, Fe 2.26-4.91 and Zn 1.40-2.59 (mg/100g) greater in the blends. As for the breads, significant variations were K 157.36-296.29, Ca 22.61-60.94, Mg 32.78-70.54, Fe 2.98-7.47, and Zn 1.56-7.47 (mg/100g) lower in wheat bread and bread containing fermented CF. Wheat bread had superior sensory attributes followed by bread with oven-dried CF but the bread with fermented CF had the poorest sensory ranking. The composite bread had better nutritive value and poorer sensory properties, demanding the use of flavour enhancing agents in order to mask the unpleasant fermented taste and aroma. Addition of dry heat treated CF to wheat flour (25:75) produced bread with overall quality comparable to wheat bread.